Atuação sociopolítica das ONG's internacionais no processo de reabilitação e reconstrução de Moçambique, 1983-2010 - Matsimbe, Hamilton Ernesto (2023)
The work is limited to the study of the transition process in Mozambique, based on the analysis of the role of International NGO's (INGO's), with special focus on the district of Chókwe, in the southern region of the country, between 1983 and 2010. Based on articles from Jornal Notícias, open interviews carried out in the towns and villages of Lionde, Massavasse, Conhane, Nwachicoloane, Hókwe and the city of Chókwe, this thesis analyzes the contribution of INGO's in the process of reconstruction and rehabilitation of Mozambique, in view of the combined effects of the economic crisis, war and natural disasters, with special focus on drought, floods and floods. As an argument, the thesis advances that, despite the crisis resulting from the political and economic options assumed by the FRELIMO government, after independence, the hegemonic role of INGO's in emergency programs and humanitarian assistance in Mozambique results from the geopolitical context the end of the 1970s. The fall of the USSR and the advance of capitalism justified the prominence of INGO's in Mozambique, and not the discourse of their effectiveness, conveyed in the context of the New International Economic Order (NOEI) and of growing neoliberalization. However, the process coincides with an economic crisis, exacerbated by the war triggered by RENAMO and prolonged droughts, interspersed with periods of floods.